THE SPECIFICITY OF IMPLEMENTATION IN NATIONAL LEGISLATION OF INTERNATIONAL LEGAL MEANS OF PROHIBITING AND PREVENTING THE ILLICIT IMPORT, EXPORT AND TRANSFER OF OWNERSHIP OF CULTURAL PROPERTY - Мартыненко, Игорь (Teisė, 2017)
The article discusses the features of the implementation in domestic law of international legal norms contained in the Convention, UNESCO and UNIDROIT of Prohibiting and Import, Export and Transfer of Ownership of Cultural Property. Analyzing the content of the main international agreements adopted in this sphere, the author reveals trends in the creation of international obligations pursuant to special services, providing control over the movement of cultural property across the customs (state) border. Examples of experience of some European countries.